2015
DOI: 10.13189/ujph.2015.030201
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the Danger Signs and Health Seeking Behaviour of Mothers in Childhood Illness in Karachi, Pakistan

Abstract: Introduction: Maternal behaviour regarding child health care has been recognized as an important social and anthropological factor explaining high mortality rates among children under five years of age. Delays in seeking appropriate health care is known to be the largest risk behaviour which contribute large number of child deaths in developing countries especially in Pakistan. Mothers are mostly responsible for their child health, however, the importance of knowledge among mothers while in identifying the dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…However, it was higher than a study conducted in Edo state, Nigeria (35.9%) [19]and Tenta district, Amhara region (41.3%) [16]. In contrast, it was lower than a study conducted in Pakistan (81.1%) [20], Bahir Dar (72.7%) [21] and facility based study conducted in Ambo town, Central Ethiopia, (60.5%) [22]. These discrepancies might be due to social environment that does not encourage health care seeking behavior towards neonatal danger signs, difference in accessibility of health facilities and the time duration in this study was limited to twenty-four hours since the onset of neonatal danger sign.…”
Section: Discussioncontrasting
confidence: 62%
“…However, it was higher than a study conducted in Edo state, Nigeria (35.9%) [19]and Tenta district, Amhara region (41.3%) [16]. In contrast, it was lower than a study conducted in Pakistan (81.1%) [20], Bahir Dar (72.7%) [21] and facility based study conducted in Ambo town, Central Ethiopia, (60.5%) [22]. These discrepancies might be due to social environment that does not encourage health care seeking behavior towards neonatal danger signs, difference in accessibility of health facilities and the time duration in this study was limited to twenty-four hours since the onset of neonatal danger sign.…”
Section: Discussioncontrasting
confidence: 62%
“…However, IMCIS implemented in Low and Middle-income Countries (LMIC) specifically in SSA has not achieved its target [ 17 ]. Mothers or caregivers play a crucial role in recognizing the symptoms of acute respiratory infection in under-five children [ 18 , 19 ]. Previous studies conducted on mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children showed that maternal education [ 20 , 21 ], household wealth status [ 19 , 22 ], distance to a health facility [ 23 , 24 ], residence [ 20 , 25 ], childhood nutritional status [ 19 , 26 ], maternal occupation [ 22 , 27 ], husband education [ 28 ], perceived severity [ 20 , 21 , 29 ], previous history of under-five death [ 20 ], media exposure [ 14 ], ANC visit [ 30 ], and place of delivery [ 31 , 32 ] were found to be significant predictors.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in the mortality rate of under-five children is improved from 1.8% by the year of1990-2000 to 3.9% from 2000-2015 worldwide (Awasthi, Verma & Agarwal, 2018). Global community permitted Sustainable Development Goal (SDG) at the termination of Millenium Development Goal to reduce avoidable deaths of under-five children (Anwar-ul-Haq, Kumar & Durrani, 2019).…”
Section: Introductionmentioning
confidence: 99%